The Influence of Knowledge Attributes on Interpersonal Distrust in Knowledge Hiding - Ivan Ivan; Elsye Tandelilin (Return : Study of Management, Economic and Bussines, 2025)
This study aims to test and analyze the influence of the theory of knowledge management, which includes psychological danger, interpersonal distrust, knowledge hiding, knowledge attribute, and compassion training on employees in paper mills. The type of research used is basic research, utilizing four variables and one moderation variable, namely psychological danger, interpersonal distrust, knowledge hiding, knowledge attribute, and compassion training as the moderation variable. This study used primary data by distributing an online questionnaire involving 123 respondents as a sample and was analyzed using the SEM (Structural Equation Modeling) method with SPSS 25 and AMOS Graphics 22.0 software. The results of the study showed that all hypotheses were supported: psychological danger had a significant positive effect on interpersonal distrust; psychological danger had a significant positive effect on knowledge hiding; interpersonal distrust had a significant positive effect on knowledge hiding; compassion training had a significant positive effect on the influence of psychological danger on interpersonal distrust; and knowledge attribute had a significant positive effect on interpersonal distrust.